Albrek's tomb / 3. - Forman, Mark, 1964- (Adventurers wanted, 2013)
Newly-named wizard Alexander Taylor joins a familiar company of adventurers on a new quest to discover the fate of the legendary dwarf Albrek, find his mythical tomb, and locate the lost talisman that could be the key needed to save the entire dwarf realm.